Discovery of new non-symmetrical heterocyclic pentanoid derivatives targeting metastatic triple-negative breast cancer - Khor, Poh Yen; Stanslas, Johnson; Rasol, Nurulfazlina Edayah; Chan, Kok Meng; Mock, Phooi Yan; Lam, Kok Wai (Elsevier, 2025)
This study describes the synthesis and structure-activity relationship (SAR) analysis of non- symmetrical heterocyclic pentanoid derivative as potential anti-cancer agents. The lead compound, 5d, exhibited potent (IC50 = 0.38 ± 0.05 μM) and selective (Selectivity Index: 2–9) growth inhibitory effects on the metastatic triple-negative breast cancer (TNBC) cells. Mechanistic studies revealed that 5d attenuates proteasomal degradation activity via the ubiquitin-proteasome pathway, leading to G2/M phase cell cycle arrest and the induction of apoptotic cell death.